System flexibility provision using short term grid scale storage. Issue 3 (1st February 2016) - Devlin, Joseph; Li, Kang; Higgins, Paraic; Foley, Aoife
Abstract : This study presents a novel analysis of the utilisation of grid scale energy storage to mitigate negative system operational impacts due to high penetrations of wind power. This was investigated by artificially lowering the minimum stable generation level of a gas thermal generating unit coupled to a storage device over a five hour storage charging window using a unit commitment and economic dispatch model. The key findings of the analysis were a 0.18% reduction in wind curtailment, a 2.35 MW/min reduction in the ramping rate required to be met by all generators in the test system during a representative period and a total generation cost reduction of €6.5 million.